Exploring the Multitarget Potential of Iridoids: Advances and Applications - Grover, Parul; Mehta, Lovekesh; Malhotra, Anjleena; Kapoor, Garima; Nagarajan, Kandasamy; Kumar, Parvin; Chawla, Viney; Chawla, Pooja A. (Current Topics in Medicinal Chemistry, 2023)
Iridoids are secondary plant metabolites that are multitarget compounds active against various diseases. Iridoids are structurally classified into iridoid glycosides and non-glycosidic iridoids according to the presence or absence of intramolecular glycosidic bonds; additionally, iridoid glycosides can be further subdivided into carbocyclic iridoids and secoiridoids. These monoterpenoids belong to the cyclopentan[c]-pyran system, which has a wide range of biological activities, including antiviral, anticancer, antiplasmodial, neuroprotective, anti-thrombolytic, antitrypanosomal, antidiabetic, hepatoprotective, anti-oxidant, antihyperlipidemic and anti-inflammatory properties. The basic chemical structure of iridoids in plants (the iridoid ring scaffold) is biosynthesized in plants by the enzyme iridoid synthase using 8-oxogeranial as a substrate. With advances in phytochemical research, many iridoid compounds with novel structure and outstanding activity have been identified in recent years. Biologically active iridoid derivatives have been found in a variety of plant families, including Plantaginaceae, Rubiaceae, Verbenaceae, and Scrophulariaceae. Iridoids have the potential of modulating many biological events in various diseases. This review highlights the multitarget potential of iridoids and includes a compilation of recent publications on the pharmacology of iridoids. Several in vitro and in vivo models used, along with the results, are also included in the paper. This paper's systematic summary was created by searching for relevant iridoid material on websites such as Google Scholar, PubMed, SciFinder Scholar, Science Direct, and others. The compilation will provide the researchers with a thorough understanding of iridoid and its congeners, which will further help in designing a large number of potential compounds with a strong impact on curing various diseases.
Keywords: Polypharmacology